TINJAUAN PENGGUNAAN MODEL DINAMIKA SISTEM (SYSTEM DYNAMICS) DALAM KEBIJAKAN KESELAMATAN TRANSPORTASI - Mukti, Elsa Tri; Sjafruddin, Ade; Kusumawati, Aine (FSTPT Indonesia, 2015)
In a complex system, such as in the field of transportation safety, the problem is actually present in the basic structure of the system. Therefore, an analysis of the system needed to be able to solve problems in a comprehensive manner, so we need a form of settlement by using a systems approach. A systems approach is not only in regards to theory, but also the way of thinking and practical philosophy in solving a problem. System dynamics model under system approach methodology set completion cohesive steps to be followed systematically by understanding basic cause of every problem under consideration. By providing insight into the feedback process, system dynamics models provide a better understanding of the users of the system to understand the dynamic behavior of a system.